Co-hydrothermal carbonization of polyvinyl chloride and corncob for clean solid fuel production. (April 2020) - Lu, Xiaoluan; Ma, Xiaoqian; Chen, Xinfei; Yao, Zhongliang; Zhang, Chaoyue
Highlights: The effect of corncob/PVC mass ratio and feedwater pH during co-HTC was studied. The experimental efficiency was higher than calculated value in dechlorination. The addition of corncob waste and citric acid can improve the hydrochars quality. Abstract: The improvement of dechlorination efficiency remains an important challenge during co-hydrothermal carbonization (co-HTC) of polyvinyl chloride (PVC). In this work, co-HTC of biomass and PVC at different mixing ratios (30%–70%) and feed-water pH (3–11) was proposed to further improve the dechlorination efficiency. In terms of water solvent, the dechlorination efficiency of co-HTC process (87.83%–93.63%) was higher than that of individual HTC of polyvinyl chloride (87.44%). In case of organic acid/alkali solvents, the dechlorination efficiency further increased to 95.20% at pH = 5. Particularly, the hydrochars derived from co-HTC showed high fuel ratio (0.71–0.99) and their higher heating value reached approximately 29.16–32.83 MJ/kg. The TGA results showed that the combustion behaviors of hydrochars derived from co-HTC got better compared with that of hydrochar derived from PVC. Therefore, co-HTC can realize sustainable utilization of PVC towards clean solid fuels. This work also sheds light on the potential of organic acid in dechlorination treatment.